A review of the Caryanda tamdaoensis species-group (Orthoptera: Acrididae), with description of a new species from Yunnan, China - Song, Hong; Yin, Zhi-Long; Storozhenko, Sergey Yu.; Mao, Ben-Yong (Zootaxa, 2024)
The species composition of the Caryanda tamdaoensis species-group (Acrididae: Caryandinae: Caryanda Stål, 1878) is discussed. A new species, Caryanda hongheensis Mao, Yin & Song, sp. nov., is described and illustrated from China. A new synonymy is proposed: Caryanda tamdaoensis Storozhenko, 1992 = Caryanda aurata Mao, Ren & Ou, 2007, syn. nov. The name of the Caryanda aurata species-group is accordingly replaced by the Caryanda tamdaoensis species-group. Caryanda azurea Gorochov & Storozhenko, 1994 is divided into two subspecies: Caryanda azurea azurea stat. nov. from Vietnam and Caryanda azurea colourfula Mao, Ren & Ou, 2011, stat. nov. from China. A key to the species and two subspecies of this species group is given. All species are illustrated.